Effects of group cognitive behavioral therapy on clinical efficacy and executive function in patients with generalized anxiety disorder - Lyu Longqin; Mu Jingping; Liao Heng; Liu Lizhu; Wang Xi (Sichuan jingshen weisheng, 2024)
BackgroundPrevious studies have found that patients with generalized anxiety disorder （GAD） have impaired performance in executive function， and group cognitive behavioral therapy （CBT） has been shown to be effective in alleviating negative affect in patients with GAD， while its efficacy on executive function remains unclear.ObjectiveTo explore the efficacy of group CBT on anxiety symptom and executive function in GAD patients， so as to provide references for the rehabilitation program for GAD.MethodsA total of 80 consecutive patients with GAD who were hospitalized in Sleep and Psychosomatic Medical Center of Shiyan Taihe Hospital from March 2021 to August 2022 and met the Diagnostic and Statistical Manual of Mental Disorders， fifth edition （DSM-5） diagnostic criteria for GAD were enrolled， and they were assigned into study group （n=40） and control group （n=40） using random number table methods. All patients were subjected to routine medication treatment and regular health education， based on this， study group received group CBT once a week （6 weeks， 60 to 90 minutes per session）. At the enrollment and after 6 weeks of treatment， patients were assessed using Hamilton Anxiety Scale （HAMA） and Frontal Assessment Battery （FAB）.ResultsANOVA with repeated measures on HAMA score revealed a significant time effect （F=1 870.320， P<0.01）， no significant group effect and no significant time×group interaction effect （F=1.254， 0.293， P>0.05）. Significant time effect， group effect and time×group interaction effect were reported on FAB scores （F=311.190， 4.399， 7.021， P<0.05 or 0.01）. Further analysis indicated that FAB scores of both groups after treatment were higher than those at baseline （t=200.569， 115.401， P<0.01）.And the FAB score of study group was higher than that of control group after treatment （t=-3.211， P<0.01）.ConclusionGroup CBT combined with medication treatment for GAD may alleviate the anxiety symptoms and improve executive function in GAD patients. ［Funded by Shiyan Science and Technology Bureau Pilot Scientific Research Project （number， 21Y21）］